A STUDY ON NPAS OF SELECTED PRIVATE & PUBLIC SECTOR BANKS IN INDIA - Javheri, Jayraj; Gawali, Ravindra (Indian Journal of Finance and Banking, 2022)
Banks play a very important role in any Financial System. It is the backbone of the Indian Financial System. The Rising NPA’s of the Banks in India for the last 5 years has really posed a threat to the Indian financial system. Recently Standard & Poor Global Rating agency has expected the NPA’s of Indian banks to remain elevated at 11.5 %. NPA helps to measure the Performance of any bank. It is quite evident that the Recent Covid Pandemic has badly hit not only India but the entire world to a greater extent. The Public and Private sector banks in India both have been adversely affected by the Rising NPA. Through this research, it has been observed that Public sector banks are more adversely affected than Private sector banks. My Study Focus on the Trend & Differences in the Non-Performing Assets of the Selected Indian Public and Private Sector Banks.JEL Classification Codes: E, G.